Hydrocarbon measurements during tropospheric ozone depletion events : evidence for halogen atom chemistry - Ramacher, B.; Koppmann, R.; Rudolph, J. (Journal of Geophysical Research: Atmospheres, 1999)
During the Arctic Tropospheric Ozone Chemistry 1996 (ARCTOC 96) field campaign (March 29 to May 15, 1996), in situ measurements of C-2-C-8 hydrocarbons, selected C-1-C-2 halocarbons, and carbon monoxide were carried out at Ny Alesund, Svalbard (78 degrees 55'N, 11 degrees 56'E). Two major tropospheric ozone depletions were observed during this period. In each case, concurrent depletion of alkanes and ethyne but no significant changes in benzene, chloromethane, or CO mixing ratios were detected. The change in the propane/benzene ratio can be used as evidence for the presence of chlorine radicals. Time integrated chlorine and bromine atom concentrations were calculated from the concentration changes of light alkanes and ethyne, respectively. At background ozone mixing ratios (O-3 > 30 ppbv) our calculations yielded no significant integrated halogen atom concentrations (Cl: 5 +/- 14 x 10(8) s cm(-3), Br: 9 +/- 42 x 10(10) s cm(-3)). During ma ozone depletion events, these values increase by more than a factor of 10 to values of about 10(10) s cm(-3) (Cl) and 5 x 10(12) s cm(-3) (Br). For such events the observed ozone losses can be explained quantitatively with these data. Our results show that free bromine atoms appear to be the major cause for ozone depletion (more than 92%). The contribution of chlorine atoms to the ozone loss is of the order of 1% or less. Highest integrated chlorine and bromine atom concentrations were found at lowest ozone mixing ratios and reached up to 1.4 x 10(10) and 1.4 x 10(13) s cm(-3), respectively. A closer analysis reveals that during each ozone depletion event the integrated chlorine atom concentration increases earlier than the integrated bromine atom concentration and remains at high levels for a longer period of time. The bromine atom concentration starts to increase when ozone mixing ratios are below 15-20 ppbv and reaches very high levels for ozone <5 ppbv. The integrated chlorine concentration appears to be anticorrelated to the ozone mixing ratio (r(2) = 0.811), ...